An Analysis of Consonant Pronunciation Errors by EFL Preschool Children (5-Years-Old): Distinctive Features Approach - Wuwur, Fransiska Inapaska; Subiyanto, Agus (Institut Agama Islam Negeri (IAIN) Curup, 2023)
English students as second language learners must prioritize pronunciation. This study examines the pronunciation errors involved in the pronunciation of English consonants in Preschool Children (5 years), evaluates the analysis using a distinctive features approach based on Schane (1973), and discovers the possible factors that cause the errors. This study uses a descriptive qualitative approach. The data for this study came from listening to and observing the natural pronunciation of three Indonesian preschool. The writer analyzed the data, identified errors in children's pronunciation, classified, discovered, and concluded the data. As a result, most 5-year-old preschoolers make consonant pronunciation errors. Students mispronounce eight consonants. They are [tÊƒ], [Ê¤], [Î¸], [s, [z], [Êƒ], and [v]. The sound [tÊƒ] is changed by the sound [k], [Ê¤] is changed by the sound [d], [Î¸] is changed by the sound [t], [Êƒ] is changed by [s], and [v] is changed by [p]. Then, there is a [s] sound and a [z] sound when deletion occurs. Students also make articulation errors because some English consonant sounds do not exist in Indonesian, which is one of the factors that allows students to replace or change English sounds.